Shelf Inputs and Lateral Transport of Mn, Co, and Ce in the Western North Pacific Ocean - Morton, Peter L.; Landing, William M.; Shiller, Alan M.; Moody, Amy; Kelly, Thomas D.; Bizimis, Michael; Donat, John R.; De Carlo, Eric H.; Shacat, Joseph (Frontiers in Marine Science, 2019)
The margin of the western North Pacific Ocean releases redox-active elements like Mn, Co, and Ce into the water column to undergo further transformation through oxide formation, scavenging, and reductive dissolution. Near the margin, the upper ocean waters enriched in these elements are characterized by high dissolved oxygen, low salinity, and low temperature, and are a source of the North Pacific Intermediate Water. High dissolved concentrations are observed across the Western Subarctic Gyre, with a rapid decrease in concentrations away from the margin and across the subarctic-subtropical front. The particulate concentrations of Mn, Co, and Ce are also high in the subarctic surface ocean and enriched relative to Ti and trivalent rare earth elements. Furthermore, the particles enriched in Mn, Co, and Ce coincide at the same depth range, suggesting that these elemental cycles are coupled through microbial oxidation in the subarctic gyre as the waters travel along the margin before being subducted at the subarctic-subtropical front. Away from the margin, the Mn, Co, and Ce cycles decouple, as Mn and Ce settle out as particles while dissolved Co is preserved and transported within the North Pacific Intermediate Water into the central North Pacific Ocean.